IMPACT ON GABA RECEPTOR, SAFETY MEASURES AND ONSET OF ACTION ON BENZODIAZEPINES DOSE - Disuza, Pro.Methwe Disuza (International Journal of Multidisciplinary Research and Studies, 2021)
The main objective of this study is to understand the benzodiazepines, their onset of action, and duration of action because it is mainly used as a tranquilizer in most cases; Benzodiazepines have a dose-dependent therapeutic effect, higher adverse effect on high dose administration. Mainly uses anxiety and panic seizures (convulsions), and insomnia or trouble sleeping, general anesthesia, sedation prior to surgery or diagnostic procedures, muscle relaxation, alcohol withdrawal and drug-associated agitation, nausea and vomiting, depression, and panic attacks.